PEMETAAN AREAL POTENSI KONFLIK IZIN USAHA PEMANFAATAN HASIL HUTAN KAYU HUTAN TANAMAN (IUPHHK-HT) BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) PADA PT. RAPP ESTATE MANDAU - Muhammad Ikhwan (Fakultas Pertanian, Universitas Riau, 2016)
Information on potential areas of conflict is very important and the information required by stakeholders in the conflict control activities plantations. Presentation of spatial data will further help provide a clear and accurate information on the location, the distance between the location and accessibility of potential areas of conflict with existing security resources in the field. This study aims to map out potential areas of conflict in the Business License Utilization of Wood Forest Plants (IUPHHK-HT) PT. RAPP Estate Saber. This study was conducted in May 2014 s.d. July 2014 and the location of this research is the Business License Utilization of Wood Forest Plants (IUPHHK-HT) PT. RAPP Estate Saber located in Siak regency, Riau Province. The method used in this research is the analysis of overlay with a predefined scoring. Research shows it is known that IUPHHK-HT PT RAPP Estate Saber area which was dominated by the level of potential conflict with an area 12499.87 ha (71.59%) for class A potential, 3047.43 ha (17.45%) for the potential class, and 1913.70 ha (10.96%) for very potential class.